A national analysis of patterns of care and outcomes for adults diagnosed with desmoplastic small round cell tumors in the United States. Issue 7 (6th March 2019) - Gani, Faiz; Goel, Utkarsh; Canner, Joseph K.; Meyer, Christian F.; Johnston, Fabian M.
Abstract: Background: Because of the rarity of desmoplastic small round cell tumors (DSRCT), there is a lack of data describing patterns of care and survival for these patients. Using a national tumor registry, the current study sought to describe patterns of care and clinical outcomes for patients with DSCRT. Methods: Data from the National Cancer Database were used to identify 491 patients aged 18 years or older diagnosed with DSRCT between 2004 and 2014. Multivariable Cox proportional hazards regression analysis was used to identify factors associated with overall survival (OS). Results: Among all patients, 41.2% (n = 200), underwent surgical resection of their primary tumor, chemotherapy was administered to 86.5% (n = 415) of patients, while radiation therapy was administered to 13.0% (n = 63) of patients. Over the study, 69.7% of patients died with a median OS of 25.9 months (interquartile range [IQR]: 22.7‐27.5); 1‐, 3‐, and 5‐year OS were 78.6%, 32.3%, and 18.4%, respectively. On multivariable analysis, stage IV disease (Hazard ﻿Ratio [HR] = 2.12, 95% CI: 1.41‐3.18), receipt of surgery (HR = 0.68, 95% CI: 0.50‐0.91), chemotherapy (HR = 0.52, 95% CI: 0.35‐0.78), or radiation therapy (HR = 0.55, 95% CI: 0.33‐0.92) were independently associated with OS. Conclusions: Although receipt of multimodality treatment may lead to improved survival, further research and clinical trials are required to establish best practices for the care of DSRCT.